Tender are the feet - Lin, Aung; Thein, Master; Tint, Diamond Bo (Edition filmmuseum, 2018)
"Sein Lin, the drummer for a traditional Burmese dance theatre group in Rangoon, falls in love with beautiful dancer Khin San. When she leaves the group to pursue a career as a film actress, he gives her a small figure as a keepsake, a symbol of traditional theatre." [imdb.com]